Dampak Perundungan Pada Aktivitas Belajar Siswa SMPN 42 Palembang - Oktariana, Nurlaila; Harapan, Edi; Fauzi, Taty (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
The phenomenon of bullying often occurs not only in Indonesia, but also in other parts of the world and can be experienced by everyone. Cases of bullying in Indonesia have attracted the attention of many groups, especially in the world of education, which occurs in school environments. This research aims to determine the causal factors and their impact on student learning activities.  The research method used is descriptive qualitative. Data collection techniques use observation, interviews and documentation. To test the validity of the data using a credibility test with the triangulation technique. The results of this research prove that the bullying that occurred at SMP Negeri 42 Palembang, both verbally and physically, was caused by the students' inability to defend themselves, thus making the perpetrators of the bullying carry out these actions continuously. The role of the family, childhood experiences, and the school environment have an impact on bullying and learning activities. The role of guidance and counseling teachers is needed to provide counseling services to victims and perpetrators of bullying so that it does not happen again and to create a safe and comfortable environment in the school environment.